(untitled) (Dhaka University Journal of Biological Sciences, 2017)
Fifteen house flies were used to isolate bacteria from external body surface and alimentary tract. A total of 50 isolates were obtained from the house flies, of which 25 (50%) were collected from the external body surface and 25 (50%) from alimentary gut. Fifteen isolates (30%) were obtained from Shamsunnahar Hall (SN) dining room, 22 (44%) from Dhaka Medical College Hospital (DMCH) and 13 (26%) from Rokeya Hall (RH) canteen. Six Gram-negative bacteria were isolated from the house flies namely, Escherichia coli (36%), Shigella spp. (22%), Salmonella spp. (18%), Pseudomonas spp. (10%), Klebsiella spp. (8%) and Enterobacter spp. (6%). E. coli was the highest in number in all three study areas which was 33% in SN Hall dining, 36% in DMCH, and 39% in RH canteen. E. coli was present in 32 and 40% of external body surface and gut samples, respectively. Bacterial susceptibility to antimicrobial agents showed that E. coli isolates were highly resistant (66-77.7%) to ampicillin, ciprofloxacilin and penicillin antibiotics. Salmonella isolates were sensitive to chloramphenicol but it was (55.5%) resistant to ampicillin, penicillin, tetracycline, gentamycin and imipenem antibiotics. In case of Shigella and Pseudomonas, 72.72 and 80% isolates were resistant to tetracycline and chloramphenicol, respectively. Among the Enterobacter spp. 66.66% were resistant to chloramphenicol, imipenem, vancomycin and tetracycline, while Klebsiella showed 100% resistant pattern to tetracycline in the study. It was observed that house flies carry several multidrug resistant Gram-negative bacteria in their body surface and alimentary tract and played a role in the transmission of serious diseases to human. Dhaka Univ. J. Biol. Sci. 26(1): 91-99, 2017 (January)